The cultural impact of cross–border acquisitions on the accounting function : a case study / Gideon Stefan Stander - Stander, Gideon Stefan (North-West University, 2011)
Mergers and acquisitions (M&A) are one of the fastest strategic options that companies choose to face the global competitive market. This is evident from the number and the amount of growth in the value of the deals, as well as the occurrence of the 'mega–mergers' in recent times. If companies do not adapt to the fast moving and evolving business environment, they will run the risk of becoming obsolete. The key principle behind buying a company is to create shareholder value, which will give the organisation a competitive advantage. The reasoning behind M&A is that one combined company may be more valuable than two separate companies. Despite the popularity of M&A, 60–80% of M&A fail to create value. There are several reasons why M&A fail, such as the insufficient analysis and examination during the planning and early stages of the transaction, overpayment and poor management in the integration phase. In the past 20 years, the volume of cross–border acquisitions has increased nearly three times faster than the volume of domestic acquisitions. Although cross–border M&A have become more popular, it comes with its own challenges and problems. The companies that enter into cross–border acquisitions need to face the issue of cultural differences, which is one of the common reasons of M&A failure. The participants of both companies need to integrate with the national and corporate cultures of the new company. In order for companies to be successful, the management needs to consider the impact and importance of these cultural differences. Organisations frequently struggle with cross–cultural issues and it has been argued that the cultural distance between the country of the acquirer and the acquired is an important determinant of the success of cross–border acquisitions. In the example of the German company Daimler Benz and the American company Chrysler Corporation the fact that these two companies have very different cultural backgrounds and that their structures differed significantly complicated the merger. The company's choice of languages, images, metaphors and rhetorical strategies had a huge impact on the acceptance of the merger by the employees. Hofstede investigated the social dimensions of culture in order to develop a comprehensive model of culture. The model was developed on data collected from the IBM study of work–related attitudes of 116,000 employees in over 50 countries and three regions. The first four dimensions of culture were derived from this study namely, Power Distance Index (PDI), Individualism (IDV), Masculinity (MAS), and Uncertainty Avoidance Index (UAI). Gray extended Hofstede's earlier cultural framework to an accounting perspective and suggested that accounting values are derived from cultural dimensions. Gray summarised his accounting values as: Professionalism versus statutory control, uniformity versus flexibility, conservatism versus optimism and secrecy versus transparency. The research question and objective of this study was to investigate the potential impact of cultural differences of cross–border acquisitions on companies from an accounting perspective. In order to answer the research question there were three objectives set. The first objective is to investigate the impact that cultural differences have on a company using Hofstede's cultural dimensions, the second objective is to investigate the impact that cultural differences have towards an accounting perspective using Gray's accounting values. The third and final objective of this research is to interpret the potential impact of a cross–border acquisition on a company taking the cultural differences into account. Considering the cultural differences, it was evident that there are differences between cultures, which may lead to cultural conflict and may hamper the success of cross–border mergers or acquisitions. The cultural differences that were observed, which was extended to an accounting perspective indicated that cultures do have an effect on the way accounting is done form one country to another. The conclusion can be made that companies do need to take the cultural differences into account before entering into cross–border mergers and acquisitions, and that proactive measures needs to be in place in order for the cross–border merger and acquisition to be a success. === Thesis (M.Com. (Management Accountancy))--North-West University, Potchefstroom Campus, 2011.